2021
DOI: 10.1007/s12021-021-09540-9
|View full text |Cite
|
Sign up to set email alerts
|

Controlling for Spurious Nonlinear Dependence in Connectivity Analyses

Abstract: Recent analysis methods can capture nonlinear interactions between brain regions. However, noise sources might induce spurious nonlinear relationships between the responses in different regions.Previous research has demonstrated that traditional denoising techniques effectively remove noiseinduced linear relationships between brain areas, but it is unknown whether these techniques can remove spurious nonlinear relationships. Among existing denoising methods, CompCor has been hypothesized to remove noise in BOL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…These 80 voxels served as the FFA ROI for our analyses. This procedure has additionally been reported in Fang et al (2019) and Poskanzer et al (2021).…”
Section: Hermite Polynomialsmentioning
confidence: 63%
See 2 more Smart Citations
“…These 80 voxels served as the FFA ROI for our analyses. This procedure has additionally been reported in Fang et al (2019) and Poskanzer et al (2021).…”
Section: Hermite Polynomialsmentioning
confidence: 63%
“…This suggests that our model is capable of capturing existing nonlinear interactions, but that the magnitude of these interactions in the fMRI data we analyzed is small. Additionally, our current model has outperformed previous models attempting to capture the nonlinear interactions with the FFA within this same dataset (Poskanzer et al, 2021). In sum, the small effect size of the nonlinearities appears to be a feature of the data, and not a consequence of the chosen model.…”
Section: Potential Pitfalls In the Search For Nonlinearitiesmentioning
confidence: 71%
See 1 more Smart Citation
“…This suggests that our model is capable of capturing existing nonlinear interactions, but that the magnitude of these interactions in the fMRI data we analyzed is small. Additionally, our current model has outperformed previous models attempting to capture the nonlinear interactions with the FFA within this same dataset [36]. In sum, the small effect size of the nonlinearities appears to be a feature of the data, and not a consequence of the chosen model.…”
Section: Potential Pitfalls In the Search For Nonlinearitiesmentioning
confidence: 71%
“…While linear models of connectivity are most commonly used to characterize regional interactions, several studies have reported evidence of significant nonlinear relationships between brain areas (Friston et al, 1994 ; Stephan et al, 2008 ; Marinazzo et al, 2011 ; Poskanzer et al, 2022 ). Despite nonlinear dynamics having been found across the brain, however, linear models remain popular due to sufficient performance and enhanced interpretability.…”
Section: The Puzzle Of Nonlinearitymentioning
confidence: 99%